2018
DOI: 10.1002/jbio.201800149
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal therapy enhanced the effectiveness of imiquimod against refractory cutaneous warts through boosting immune responses

Abstract: Refractory cutaneous warts are difficult to eliminate. In situ photo-immunotherapy (ISPI) is an innovative treatment concept combining local photothermal therapy (PTT) and topical immunotherapy using imiquimod. To compare the efficacy of ISPI vs topical imiquimod alone, a prospective randomized controlled trial was performed with patients suffering from refractory cutaneous warts. In both groups, approximately 50% of the skin surface containing warts was treated for 6 weeks. On the basis of topical imiquimod, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A cohort study 56 showed warts were more persistent and refractory to treatment in organ transplant recipients. In an RCT in 2018, 57 the included refractory warts were those that lasted for more than 2 years and failed response to more than two treatment methods (laser surgery, electrosurgery, curettage, liquid nitrogen freezing therapy, and topical salicylic acid treatment). In an observational study, 58 refractory warts were those resistant to conventional treatments and there was no improvement after trying different methods.…”
Section: Resultsmentioning
confidence: 99%
“…A cohort study 56 showed warts were more persistent and refractory to treatment in organ transplant recipients. In an RCT in 2018, 57 the included refractory warts were those that lasted for more than 2 years and failed response to more than two treatment methods (laser surgery, electrosurgery, curettage, liquid nitrogen freezing therapy, and topical salicylic acid treatment). In an observational study, 58 refractory warts were those resistant to conventional treatments and there was no improvement after trying different methods.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies consistently demonstrated that NIR irradiation along with topical imiquimod application induced release of DAMPs suppressing tumor growth in breast and skin cancer models in mice. 34 Following these in vivo results in animal models, the combination of PTT and immunologic adjuvants for refractory cutaneous warts 35 and immune checkpoint inhibitors for melanoma 36 was tested and proved effective in clinical studies.…”
Section: Cancer Photomedicinementioning
confidence: 99%
“…In response to this, DCs are stimulated and produce IFN‐γ and increase their expression of MHCII and CD80 and recruitment of DCs and T cells in tumor microenvironment. Consistently, a 10‐minutes treatment with 805‐808 nm light at an irradiance of 1‐1.5 W/cm 2 along with topical imiquimod application has been shown to induce release of damage‐associated molecular patterns (DAMPs) (HSP70, HSP90, and HMGB1) suppressed tumor growth in mammary tumor and skin squamous cell carcinoma in humans and mice, and melanoma and refractory cutaneous warts in humans . In this approach, immunogenic cell death also provides sources of tumor neoantigens, creating an in situ autologous cancer vaccine.…”
Section: Ultrashort Pulsed Laser Adjuvantmentioning
confidence: 99%